Reverse Expression of Aging-Associated Molecules through Transfection of miRNAs to Aged Mice - Jung-Hee Kim; Bo-Ram Lee; Eun-Sook Choi; Kyeong-Min Lee; Seong-Kyoon Choi; Jung Hoon Cho; Won Bae Jeon; Eunjoo Kim (Elsevier, 2017)
Molecular changes during aging have been studied to understand the mechanism of aging progress. Herein, changes in microRNA (miRNA) expression in the whole blood of mice were studied to systemically reverse aging and propose them as non-invasive biomarkers. Through next-generation sequencing analysis, we selected 27 differentially expressed miRNAs during aging. The most recognized function involved was liver steatosis, a type of non-alcoholic fatty liver disease (NAFLD). Among 27 miRNAs, six were predicted to be involved in NAFLD, miR-16-5p, miR-17-5p, miR-21a-5p, miR-30c-5p, miR-103-3p, and miR-130a-3p; alterations in their blood and liver levels were confirmed by real-time qPCR. The expression of the genes associated in the network of these miRNAs, Bcl2, Ppara, E2f1, E2f2, Akt, Ccnd1, and Smad2/3, also was altered in the liver of aged mice. Following transfection of these miRNAs into 18-month-old mice, levels of miR-21a-5p, miR-103-3p, and miR-30c-5p increased, and their related genes exhibited a reversed expression in the liver. Expression of Mre11a, p16INK4a, and Mtor, reported to be aging-associated molecules, also was reversed in the livers of miRNA-transfected mice. These miRNAs could be non-invasive biomarkers for aging, and they might induce a reverse regulation of aging-associated pathways. This study provides preliminary data on reverse aging, which could be applied further for treatments of adult diseases. Keywords: reverse aging, circulating miRNA, aging biomarker, non-alcoholic fatty liver disease, telomerase